2016
DOI: 10.1177/0734242x16649680
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions of waste management processes and options: A case study

Abstract: Increasing concern about climate change is prompting organisations to mitigate their greenhouse gas (GHG) emissions. Waste management activities also contribute to GHG emissions. In the waste management sector, there has been an increasing diversion of waste sent to landfill, with much emphasis on recycling and reuse to prevent emissions. This study evaluates the carbon footprint of the different processes involved in waste management systems, considering the entire waste management stream. Waste management da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…GHG emissions are generated during the feedstock's supply to the biofuel plant. These emissions have been calculated for different feedstocks in several studies [39][40][41][42][43][44] in order to estimate the GHG emission net efficiency related to the biofuel use. Table 3 reports the GHG emission related to the collection and transport cost for pine, switchgrass, corn stover, BSGs and urban wastes, respectively.…”
Section: Cost and Ghg Emission Related To The Feedstock Collection And Transportmentioning
confidence: 99%
“…GHG emissions are generated during the feedstock's supply to the biofuel plant. These emissions have been calculated for different feedstocks in several studies [39][40][41][42][43][44] in order to estimate the GHG emission net efficiency related to the biofuel use. Table 3 reports the GHG emission related to the collection and transport cost for pine, switchgrass, corn stover, BSGs and urban wastes, respectively.…”
Section: Cost and Ghg Emission Related To The Feedstock Collection And Transportmentioning
confidence: 99%
“…Habitually, inefficient waste management practices such as open dumping and burning of waste to reduce waste volumes are still prevalent in the management of MSW in low income countries [28]. The outcome of such practices leads to emission of GHGs that contribute to climate change and global warming [29]. On global scale Malawi's contribution to GHG emission is very low; however the impacts of climate change have serious implications on the country [30].…”
Section: An Overview Of Municipal Solid Waste Globallymentioning
confidence: 99%
“…Abdel-Shafy and Mansour [17], de la Barrera and Hooda [18], and Turner et al [19], found that recycling helps in saving carbon emissions through different processes. They stipulate that GHG emissions savings can be achieved through the recycling of sourcesegregated waste materials (with some exceptions like soil, paint, plasterboard).…”
Section: Introductionmentioning
confidence: 99%